# multiply

-(-5-p)(5+p)

## -(25-p^2= p^2-25

## Not quite

-(-5-p) = 5+p

so we have (5+p)^2

## To solve the expression (-(-5-p)(5+p)), we need to use the distributive property and simplify.

Step 1: Distribute the negative sign inside the parentheses:

-(-5-p) = 5 + p

Step 2: Multiply the terms in the expanded expression:

(5 + p)(5 + p) = 5(5) + 5(p) + p(5) + p(p)

Step 3: Simplify the expression:

25 + 5p + 5p + p²

Step 4: Combine like terms:

25 + 10p + p²

Therefore, the simplified expression is 25 + 10p + p².